IDENTIFIKASI FAKTOR KEPUASAN PENGGUNA STADION SEPAK BOLA UNTAN PONTIANAK - Risky, Risky; Supriatna, Eka; Perdana, Rahmat Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to examine the factors affecting user satisfaction at the Tanjungpura University (Untan) Football Stadium in Pontianak, as well as to assess the stadium's overall management. Utilizing a quantitative descriptive research design, data were gathered through surveys conducted via questionnaires and Google Forms. The sample consisted of 64 respondents, selected through a non-probability accidental sampling technique. Data analysis was performed using Microsoft Excel. The results indicate that, in terms of product quality, 50% of respondents reported satisfaction, 8% expressed high satisfaction, 23% reported moderate dissatisfaction, and 19% were dissatisfied. Regarding pricing, 66% of participants felt less satisfied, 23% were highly satisfied, 5% satisfied, and 6% dissatisfied. For service quality, 50% were satisfied, 11% highly satisfied, 34% less satisfied, and 5% dissatisfied. As for emotional factors, 39% of respondents felt satisfied, 8% very satisfied, 36% less satisfied, and 17% dissatisfied.